Need of Administrative Structure in Government: Exploring the Impact of Public Administration Innovations on Government Performance and Citizen Expectations (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This article reviews the contribution of public administration (PA) innovations toward sustainable development and its impact on citizens’ expectations on the performance of the government. Today governments aim to modernize the public administration, to strengthen its capacities and to make it more efficient and accountable. Governments today are using different methods and techniques to find out the citizen’s demands in order to reduce the gap between government and the people and to enhance the public trust as an important factor.The aim of this paper is focused on the review of the new developments on the public administration on the frame of the challenges and process of globalization and its impact on citizens ‘expectations. Today citizens are more or less satisfied with innovations in public administration, however, it is necessity to regularly asses the achievements related to further innovations and their ability to effect the citizens life and enhance their expectations. The research methods of this paper refer to the empirical materials, comparative systematic analysis on public administration developments, archival research, policies and bibliographical analysis.